1996
DOI: 10.1104/pp.111.4.1191
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Na+ Transport in a Salt-Tolerant Charophyte (Isotopic Fluxes, Electrophysiology, and Thermodynamics in Plants Adapted to Saltwater and Freshwater)

Abstract: In salt-tolerant Chara longifolia, enhanced Na+ efflux plays an important role in maintaining low cytoplasmic Na+. When it is cultured in fresh water (FW), C. longifolia has a higher Na+ efflux than the obligate FW Chara corallina, although pH dependence and inhibitor profiles are similar for both species (1. Whittington and M.A. Bisson 119941 j Exp Bot 45: 657-665). When it is cultured in saltwater, C. longifolia has a Na+ efflux of 264 f 14 nmol m-'s-' at pH 7, 13 times higher than FW-adapted cultures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…More accurate cytosolic measurements in non-marine plants give values of 3 to 5 mm for NO 3 Ϫ in barley root epidermal cells (Walker et al, 1995;van der Leij et al, 1998) and 50 mm for Na ϩ in a salttolerant Chara species (Kiegle and Bisson, 1996). (Although total internal Na ϩ concentrations have been estimated in two species of seagrass, being around 100 mm in epidermal leaf cells and showing higher values in other tissues [Beer et al, 1980], such estimates will reflect primarily the composition of the large central vacuole rather than that of the cytosol.)…”
Section: Discussionmentioning
confidence: 99%
“…More accurate cytosolic measurements in non-marine plants give values of 3 to 5 mm for NO 3 Ϫ in barley root epidermal cells (Walker et al, 1995;van der Leij et al, 1998) and 50 mm for Na ϩ in a salttolerant Chara species (Kiegle and Bisson, 1996). (Although total internal Na ϩ concentrations have been estimated in two species of seagrass, being around 100 mm in epidermal leaf cells and showing higher values in other tissues [Beer et al, 1980], such estimates will reflect primarily the composition of the large central vacuole rather than that of the cytosol.)…”
Section: Discussionmentioning
confidence: 99%
“…Sodium transport ports occur in bacteria, animals, fungi and mosses (Benito and Rodriguez-Navarro, 2003) and are presumed to occur in all marine protists, although very few studies have been done to confirm this assumption. Sodium-transport ports have been studied in the raphidophyte Heterosigma akashiwo (Shono et al, 2001), the chytridomycete Blastocladiella emersonii (Fietto et al, 2002), and the macroalga Chara longifolia (Kiegle and Bisson, 1996). Sodium-transport physiology has also been studied in the freshwater cyanobacterium Cylindrospermopsis raciborskii (Pomati et al, 2003(Pomati et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…). Studies with radioactive Na + isotopes and amiloride have shown both salt‐tolerant C. longifolia and salt‐sensitive C. corralina to actively extrude Na + through Na + /H + antiporters (Clint & MacRobbie ; Kiegle & Bisson ). Halophilic green algae like Dunaliella viridis and D. salina also actively extrude Na + and accumulate glycerol in the cytosol for osmotic adjustment (Katz et al .…”
Section: Discussionmentioning
confidence: 99%
“…Their euryhaline species regulate turgor by taking up K + and Cl − while Na + only plays a minor role in the process. In the characean algae, Na + is actively extruded from the cytosol by a Na + /H + antiporter (Bisson & Kirst ; Kiegle & Bisson ; Bisson et al . ).…”
Section: Introductionmentioning
confidence: 99%